Experimental work on the different conditions of jasmine flowers on the composition of jasmine absolute - Nur Farhana, Mhd Razaki (2014)
Essential oil is the botanical extracts from various plant materials. The essential oils nowadays had been commercialized due to its thousands of benefits. On the other hand, Jasmine flowers had been known for its fragrance value for ages. Jasmine primarily used in perfumery industry because of its therapeutic properties. Basically, there are two types of Jasmine Essential oils, named Jasmine Concrete and Jasmine Absolute. Jasmine Absolute is the pure Jasmine essential oil processed from Jasmine concrete. Same like the other flowers, Jasmine flowers will undergo essential phases of bud, bloom and wilt. In order to get best properties for Jasmine absolute, this thesis will study about the different conditions of Jasmine flowers that will be affected the composition Jasmine absolute. To produce a Jasmine Absolute, method solvent extraction was used as it will give high yield and low cost. In this solvent extraction method, Hexane was used as the solvent. Once the concrete was obtained, it will be mixed with ethanol and then will undergo freezing and distillation process. The properties of each different condition will be then analysed using GC analysis. Based on the analysis, the dry condition give the best qualitative analysis meanwhile the bloom condition give the best quantitative analysis